Pengaruh Debt to Equity Ratio, Net Profit Margin, dan Return on Equity Terhadap Pertumbuhan Modal Sendiri Pada Perusahaan Sub Sektor Farmasi di Bursa Efek Indonesia - Iin Hendrayani; Rahmad Doni (P3M STIE Mulia Darma Pratama, 2020)
Capital growth itself is the result of a percentage of its own capital increases compared to the previous amount of capital in the company's funding. Capital growth itself is influenced by various factors, either internal or external factors of the company. These factors include: DER, NPM, ROE, ROA, ROI, profit growth, sales growth, interest rate and tax rate. In this research researcher uses one of the factors namely DER, NPM and ROE. The financial ratios used in this study are the leverage ratios that are proscribed with DER and the profitability ratios that are proscribed with NPM and ROE. The formulation of the problem in this study is: 1. How does DER, NPM and ROE influence the growth of its own capital on the company's partial pharmaceutical sub sectors?, 2. How DER, NPM and ROE influence their own capital growth on Simultaneously the company's sub-sector pharmacy?. The objectives in this study are: 1. To determine the influence of DER, NPM and ROE against the growth of its own capital in the company's partial pharmaceutical sub-sector, 2. To determine the influence of DER, NPM and ROE on the growth of its own capital in the pharmaceutical sub-sector company simultaneously. The population in this study is a pharmaceutical sub-sector company. The sampling method in this study is purposive sampling. The data analysis methods used in this study were multiple linear regression. The results of this study show that. 1. Results of partial studies show that DER has an effect on its own capital growth, NPM has no effect on its own capital growth and ROE has an effect on its own capital growth of pharmaceutical sub-sector companies in Bursa Indonesia Securities period 2012-2017. 2. Simultaneous research results show that at least one variable X (DER, NPM and ROE) has an effect on its own capital growth